Environmental flow assessment under variable conditions: a series of case studies from Costa Rica - Chavarría-Pizarro, Laura (2025)
The estimation of environmental flow in a surface water source can be determined using different methodologies that vary in complexity depending on the variables involved in their calculation. The Center for Research and Extension in Agricultural Technology and Engineering has applied several methodologies in different watersheds across the country to provide a record of environmental flow in control sections of strategic importance for water resource management. This review article seeks to integrate the information obtained from the studies conducted to establish a scientifically based record base for application by decision-makers and for future environmental flow studies. The results obtained allow for some important conclusions. For example, it was concluded that for rivers with evident environmental degradation and little use by communities, as was the case with the Birrís River, the most appropriate methodology is the hydrological one. For rivers that flow through protected areas, such as the Pejibaye River, the hydrobiological methodology was also best suited. In cases where human activities impact aquatic ecosystems, as in the case of the Pirrís River, the methodology that best suited the river was also hydrobiological. Finally, when the basins have complex characteristics and different anthropogenic uses, as is the case of the Tempisque and Sarapiquí rivers, the most appropriate methodology is the holistic one. Each of these methods was technically selected under the parameters required to calculate an environmental flow regime valid for each condition.